Compressive peroneal neuropathy by an intraneural ganglion cyst combined with L5 radiculopathy: A case report - Park, Se-Heum (Medicine (Baltimore), 2019)
RATIONALE: Most cases of foot drop are known to result from lower motor neuron pathologies, particularly lumbar radiculopathy and peripheral neuropathy, including common peroneal neuropathy. To improve the prognosis of foot drop, it is important to quickly and accurately diagnose the etiology and provide appropriate treatment. PATIENT CONCERNS: A 65-year-old female patient with a history of L4-5 intervertebral disc herniation presented with right foot drop that had developed 1 month previously. DIAGNOSIS: Electrodiagnostic examination revealed common peroneal neuropathy combined with L5 radiculopathy, with the former being the main cause of the foot drop. MRI of the right knee was performed to identify the cause of the peroneal nerve lesion, which revealed an intraneural ganglion cyst in the common peroneal nerve. INTERVENTIONS: The patient was treated by ultrasound-guided percutaneous cyst aspiration and corticosteroid injection into the decompressed ganglion, followed by strengthening exercise, electrical stimulation therapy, and prescription of an ankle foot orthosis. OUTCOMES: We confirmed regeneration of the injured peroneal nerve at the follow-up electrodiagnostic examination 12 weeks after the intervention. In addition, the manual motor power test demonstrated an increase in the ankle dorsiflexor function score by one grade. LESSONS: Diagnosing the cause of foot drop can be difficult with multiple co-existing pathologies, and consideration of various possible etiologies is the key for appropriate diagnosis and treatment. In addition to imaging modalities such as MRI, electrodiagnostic examination can help to improve diagnostic accuracy. Intraneural ganglion cyst of the common peroneal nerve is rare, but should be considered as a possible cause of foot drop.